The Ratio Legis of Article 35(a) of Law Number 23 of 2006 on Population Administration - Muhammad Rizki Nurdin Sidauruk; Rachmi Sulistyarini; Nur Chanifah (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2027)
This study aims to analyze the ratio legis underlying the enactment of Article 35 letter (a) of Law Number 23 of 2006 concerning Population Administration, which regulates the registration of marriages based on a court determination, particularly in the context of interfaith marriages. The study is motivated by a normative conflict between Article 2 paragraph (1) of Law Number 1 of 1974 concerning Marriage, which stipulates the validity of marriage based on religious law, and Article 35 letter (a) of Law Number 23 of 2006, which provides an opportunity for marriage registration through a court ruling. This research employs a normative legal research method with statutory, case, and conceptual approaches. Primary, secondary, and tertiary legal materials are analyzed using descriptive-analytical and argumentative techniques. The research gap lies in the absence of studies that specifically position Article 35 letter (a) as the central object of ratio legis analysis and connect it to the disharmony between the legal regime of marriage and population administration law. Previous studies have generally focused on the legality of interfaith marriages, human rights protection, or judicial decision analysis, without systematically examining the legislative purpose of the norm and its implications for the consistency of the national legal system. The novelty of this study lies in the reconstruction of the ratio legis of Article 35 letter (a) as an instrument of population administration, which is then analyzed within the framework of vertical and horizontal legal harmonization between the population administration regime and national marriage law. Accordingly, this study not only explains the underlying legislative intent but also proposes a regulatory harmonization construct based on the theory of legal certainty as a model for resolving normative disharmony that has not been previously offered in the literature. The findings indicate that the existence of Article 35 letter (a) generates normative disharmony, resulting in legal uncertainty and divergent interpretations in judicial practice. From a legal perspective, interfaith marriages do not fulfill the validity requirements under national marriage law. Therefore, regulatory harmonization is required to ensure legal certainty, consistency in law enforcement, and synchronization between the population administration system and marriage law.